2014
DOI: 10.1002/2014je004671
|View full text |Cite
|
Sign up to set email alerts
|

The morphology of small fresh craters on Mars and the Moon

Abstract: The depth/diameter ratio for new meter-to decameter-scale Martian craters formed in the last 20 years averages 0.23, only slightly deeper than that expected for simple primary craters on rocky surfaces. Large variations in depth/diameter (d/D) between impact sites indicate that differences between the sites such as target material properties, impact velocity, angle, and physical state of the bolide(s) are important in determining the depth of small craters in the strength regime. On the Moon, the d/D of random… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
83
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 77 publications
(96 citation statements)
references
References 53 publications
12
83
1
Order By: Relevance
“…In the present study, we observed steeper slope (0.033) compared to Daubar et al 40 for small craters, and Pike 39 for large craters ( Figure 2). A deviation from 0.2 may result due to crater degradation, measurement errors arising due to small size of craters and target properties as indicated by Daubar et al 40 for small-sized craters. Our observations also present similar deviation from 0.2 as indicated by Daubar et al 40 for the 0.2-6 km size craters.…”
Section: Characterization Of Craters Based On D/d Ratiosupporting
confidence: 48%
See 1 more Smart Citation
“…In the present study, we observed steeper slope (0.033) compared to Daubar et al 40 for small craters, and Pike 39 for large craters ( Figure 2). A deviation from 0.2 may result due to crater degradation, measurement errors arising due to small size of craters and target properties as indicated by Daubar et al 40 for small-sized craters. Our observations also present similar deviation from 0.2 as indicated by Daubar et al 40 for the 0.2-6 km size craters.…”
Section: Characterization Of Craters Based On D/d Ratiosupporting
confidence: 48%
“…Further, variations in d/D can also reflect on the target material strength, impact velocity and impact angle, which play an important role in establishing the crater depth 40 . Earlier studies have suggested that the d/D ratio decreases with the passage of time due to continuous crater degradation and material infilling 41 .…”
Section: Relation Of D/d Ratio and Spatial Ejecta Extentmentioning
confidence: 99%
“…They are typically bowl shaped with a depth/diameter ratio of 0.2 and a rim height/diameter ratio of about 0.04 [ Pike , ; Melosh , ]. Small fresh lunar craters [ Basilevsky et al ., ] and a sample of several hundred small primary craters observed in before and after images (Context Camera, CTX and HiRISE) of Mars also have depth/diameter ratios of about 0.2 [ Daubar and McEwen , ; Daubar et al ., ]. Secondary craters, if present, appear to have a depth/diameter ratio of about half (0.1) that of primary craters [ Pike and Wilhelms , ].…”
Section: Rate Of Crater Modificationmentioning
confidence: 99%
“…For craters with L ≥250 km ( v i ≥ 0.95–1.1 km/s) and D ≥60 m, we found that the median is 0.112, with an average of 0.116 and standard deviation 0.035. About 3% of craters in this size range have d / D ≥0.2, a value typical of primaries on Mars of this size [ Daubar et al , ; Watters et al , ]. For craters with D ≥100 m in this range ( L ≥250 km) we found that the median is 0.127, with an average of 0.130 and standard deviation 0.033.…”
Section: Resultsmentioning
confidence: 99%
“…Simple primary impact craters on Mars that exhibit signs of good preservation have h / D ≈0.035 and d / D = 0.18 ± 0.04 [ Watters et al , , Table 3]. For fresh small primaries ( D < 35 m), d / D ≈0.23 on average [ Daubar et al , ]. That is, we find that diameter‐normalized rim heights and crater depths typical of primary craters occur in our simulations for v i ≥1.25 km/s.…”
Section: Numerical Simulationsmentioning
confidence: 99%